Elaeagnus angustifolia and its therapeutic applications in osteoarthritis - Mahboubi, Mohaddese (Industrial crops and products, 2018)
[Display omitted] •E. angustifolia fruits is used for treatment of osteoarthritis.•E. angustifolia inhibitsTNF-α, COX-1, COX-2 and IL-1β.•E. angustifolia induces some useful cytokines for treatment of osteoarthritis. Osteoarthritis as the most common type of age dependent musculoskeletal diseases is equal to “vaje-al-rakbeh” or “knee's vaje-al-mafasel” in Iranian Traditional Medicine. Elaeagnus angustifolia fruit as a popular plant in Iranian Traditional Medicine for osteoarthritis is the subject of this review article. The information was extracted from accessible international databases, electronic resources, traditional books, and inaccessible or unpublished data (R&D reports, thesis and dissertation). E. angustifolia fruits are used traditionally for treatment of osteoarthritis. There are four randomized double clinical trials on the efficacy of E. angustifolia whole fruit aqueous extract. The results of clinical trials confirmed its efficacy comparable to acetaminophen (1000 mg/day) and ibuprofen (1200 mg/day) and significant difference with placebo groups. No side effects were reported for E. angustifolia fruits (with or without seed) aqueous extract up to 600 mg/day in clinical trials. This efficacy is related to antinociceptive, anti-inflammatory and relaxant effects of E. angustifolia that are confirmed in different animal models. The anti-inflammatory effects of E. angustifolia caused by inhibition of TNF-α, COX-1, COX-2 and IL-1β and induction of some useful cytokines. Designing other clinical studies in osteoarthritis, in order to evaluate the E. angustifolia leaves ethanol or aqueous extracts is proposed.